Ni-based composite electroplating solution for in-situ generation of CeO2 based on cerium nitrate as well as preparation method and application of Ni-based composite electroplating solution
By producing CeO2 in situ on CeO2, the Ni-based composite plating solution is solved, and the problems of high porosity and poor binding force of the electroplating nickel layer are achieved, efficient and low-cost composite plating deposition is achieved, and the density and corrosion resistance of the plating are improved.
Patent Information
- Application Number
- CN202510427863.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-07
- Publication Date
- 2025-07-04
AI Technical Summary
In the prior art, electroplating nickel layer is prone to pores, resulting in accelerated corrosion, poor binding force of multi-layer nickel coating, high equipment demand and hexavalent chromium are harmful, complex processes and high costs.
A Ni-based composite plating solution based on cerium nitrate in situ generates CeO2, and a composite plating layer is deposited through a single plating solution system. The M-Ce(NO3)3 complex is uniformly dispersed in the nickel matrix, and the oxidation of Ce3+ is controlled to generate CeO2 nanoparticles, and the plating structure is optimized.
Reduce equipment investment costs by 40%, reduce production energy consumption by 25%, reduce the porosity of the coating to 0.08pores/cm2, increase the salt spray resistance time to 376 hours, reduce the residual stress by 60%, and improve the density of the coating.
Smart Images

Figure CN120250087A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of the preparation of electroplating materials, and particularly relates to a Ni-based composite electroplating solution for in-situ generating CeO2 based on cerium nitrate, and a preparation method and application thereof. Background Art
[0002] Electrodeposited nickel coatings are widely used in fields such as aerospace, automotive manufacturing, and petrochemical industry due to their excellent mechanical properties, corrosion resistance, and high-temperature resistance. However, due to the cathodic polarization during the electroplating process, the surface state of the substrate, and the improper selection of electroplating parameters, pores are likely to appear on the surface of the single-layer nickel coating, resulting in accelerated corrosion of the iron substrate during the electrochemical corrosion process. To solve this problem, the porosity is usually reduced by increasing the coating thickness, but this may affect the mechanical properties of the coating. Currently, multilayer nickel thin films (such as semi-bright nickel, high-sulfur nickel, and bright nickel) are commonly used in industry in combination with chromium thin films.
[0003] However, the existing technology still faces the following challenges: (1) The process is complex, and the use of different electroplating solutions and process conditions may increase production costs; (2) The bonding strength of the multilayer structure is poor, which is likely to cause the coating to peel off, affecting corrosion resistance and service life; (3) Internal stress problem: Multilayer nickel coatings are easily affected by internal stress. Especially during the coating process, the deposition of nickel may generate certain tensile stress or compressive stress, which may cause the coating to deform, and even cause cracks or peeling phenomena. (4) High requirements for processing and equipment: Multilayer nickel coatings usually require more precise equipment and strict process control to ensure the uniformity and appropriate thickness of each layer of the coating, which makes the technical requirements of its production process relatively high. (5) Hexavalent chromium generated in the outer chromium coating poses a hazard to human health and the environment.
[0004] Therefore, it can be seen that the above-mentioned existing technology still needs to be further improved. Summary of the Invention
[0005] One of the purposes of the present invention is to provide a Ni-based composite electroplating solution for in-situ generating CeO2 based on cerium nitrate, which realizes the deposition of a composite coating through a single electroplating solution system without the need to switch multiple electroplating solutions.
[0006] To achieve the above purpose, the present invention adopts the following technical solutions:
[0007] A Ni-based composite electroplating solution for in-situ generating CeO2 based on cerium nitrate, the raw materials and their ratios used are as follows:
[0008]
[0009] The preparation method of the described M-Ce(NO3)3 is as follows:
[0010] Step 1: Using 3,4-dihydroxybenzaldehyde and β-alanine as raw materials, pyridine as a catalyst, stirring and refluxing in a water bath under nitrogen protection for a certain period of time. Then, sodium cyanoborohydride is added to the obtained raw material solution in portions for reductive amination reaction to prepare N-(3,4-dihydroxybenzyl)-β-alanine in the form of white needle crystals.
[0011] Step 2: Dissolve the obtained N-(3,4-dihydroxybenzyl)-β-alanine and salicylaldehyde in a certain ratio. React under nitrogen protection at pH 4 - 5 to obtain a Schiff base compound.
[0012] Step 3: Dissolve the Schiff base compound and cerium nitrate hexahydrate in a certain molar ratio in anhydrous DMF. Stir and react in the dark at a temperature of 50 - 70 °C, controlling the Ce 3+ concentration to be 0.1 mol / L. Add the reaction solution to ice ether to initiate the precipitation of the complex, remove the unreacted cerium nitrate, and obtain M-Ce(NO3)3 after vacuum drying.
[0013] For the above-mentioned Ni-based composite electroplating solution based on in-situ generation of CeO2 from cerium nitrate, in Step 1, the molar ratio of 3,4-dihydroxybenzaldehyde to β-alanine is 1:1.2. 3,4-dihydroxybenzaldehyde and β-alanine are dissolved in a mixed solvent, and the mixed solvent includes ethanol and water. The solvent of the reactant obtained from the reductive amination reaction is removed by rotary evaporation, the pH is adjusted to 3 - 4 to precipitate, and after suction filtration, it is recrystallized with a mixed solvent of ethyl acetate and n-hexane to obtain N-(3,4-dihydroxybenzyl)-β-alanine.
[0014] For the above-mentioned Ni-based composite electroplating solution based on in-situ generation of CeO2 from cerium nitrate, in Step 2, the molar ratio of N-(3,4-dihydroxybenzyl)-β-alanine to salicylaldehyde is 1:1.05, and it is dissolved in absolute ethanol. React at room temperature for 10 - 15 h under nitrogen insulation to obtain a Schiff base compound.
[0015] For the above-mentioned Ni-based composite electroplating solution based on in-situ generation of CeO2 from cerium nitrate, in Step 3, the Schiff base compound and cerium nitrate hexahydrate are mixed in a molar ratio of 1:1, and the coordination process is monitored in real time by ultraviolet-visible spectroscopy during the reaction; the unreacted cerium nitrate is removed by washing with a mixed solvent of ether and acetone.
[0016] For the above-mentioned Ni-based composite electroplating solution based on in-situ generation of CeO2 from cerium nitrate, the volume ratio of ethanol to water is 7:3; the water bath temperature is 50 - 70 °C, and stir and reflux for 5 - 7 h.
[0017] The above-mentioned Ni-based composite electroplating solution for in-situ generation of CeO2 based on cerium nitrate adds sodium cyanoborohydride in three portions, and adjusts the pH to 3-4 with hydrochloric acid to precipitate; the volume ratio of ethyl acetate to n-hexane is 1:5.
[0018] In the above-mentioned Ni-based composite electroplating solution for in-situ generation of CeO2 based on cerium nitrate, in step two, the pH is adjusted to 4-5 by adding an acetic acid-sodium acetate buffer solution.
[0019] In the above-mentioned Ni-based composite electroplating solution for in-situ generation of CeO2 based on cerium nitrate, in step three, the vacuum drying temperature is 10-14 h.
[0020] Another object of the present invention is to provide a preparation method of the above-mentioned Ni-based composite electroplating solution for in-situ generation of CeO2 based on cerium nitrate, comprising the following steps:
[0021] Step one: Dissolve NiSO4, NiCl2 and H3BO3 in deionized water in sequence, and stir until transparent;
[0022] Step two: Add M-Ce(NO3)3 to the transparent solution obtained in step one, and ultrasonically disperse for 10-30 min;
[0023] Step three: Add glucose and sodium dodecyl sulfate to the ultrasonically dispersed solution obtained in step two in sequence, and magnetically stir for 20-40 min;
[0024] Step four: Adjust the pH of the reaction solution obtained in step three to 3.8-4.2, and let it stand and age for 24 h to obtain the product.
[0025] Another object of the present invention is to provide an application of the above-mentioned Ni-based composite electroplating solution for in-situ generation of CeO2 based on cerium nitrate. The application is to deposit the electroplating solution on the surface of a nickel substrate by electroplating to form a coating. By controlling the electroplating time at 20-30 minutes and the current density at 4-6 A / dm 2 , a dense coating with a thickness of 15-25 μm is obtained, and the porosity < 0.1 pores / cm 2 , which is significantly lower than that of the traditional nickel coating (the porosity is 0.5-0.8 pores / cm under the same thickness 2 ).
[0026] Compared with the prior art, the present invention brings the following beneficial technical effects:
[0027] (1) The composite coating deposition is realized through a single electroplating solution system, without the need for multi-layer electroplating solution switching and complex process control. Compared with the traditional multi-layer nickel process, the method of the present invention can reduce the equipment investment cost by about 40% and reduce the production energy consumption by 25%.
[0028] (2) During the use of the electroplating solution added with M-Ce(NO3)3, M-Ce(NO3)3 is evenly dispersed in the nickel matrix, reducing the porosity of the coating to 0.08 pores / cm 2 (ASTM B798 standard), and the salt spray test time is increased to 376 hours (compared with 120 hours for traditional nickel coatings, ASTM B117 standard).
[0029] (3) Through the co-deposition mechanism, M-Ce(NO3)3 reduces the residual stress of the coating to 45 MPa (measured by X-ray diffraction method), a 60% reduction compared to the traditional process, effectively inhibiting crack generation.
[0030] (4) When M-Ce(NO3)3 is added to the electroplating solution, under the action of M-Ce(NO3)3, the deposition potentials of cerium and nickel become closer, which can promote more cerium and nickel to deposit together, thus changing the deposition potential; therefore, the addition of M-Ce(NO3)3 can improve cathodic polarization, making the particle precipitation slower and forming a denser coating surface. Description of the Drawings
[0031] The present invention will be further described below in conjunction with the drawings:
[0032] Figure 1 It is the infrared structure diagram of M-Ce(NO3)3 prepared according to the present invention;
[0033] Figure 2 It is the XRD spectrum of M-Ce(NO3)3 prepared according to the present invention;
[0034] Figure 3 It is the surface structure and cerium element content in Example 1 of the present invention;
[0035] Figure 4 It is the surface structure and cerium element content in Example 2 of the present invention;
[0036] Figure 5 It is the surface structure and cerium element content in Example 3 of the present invention;
[0037] Figure 6 It is the surface structure and cerium element content in Comparative Example 1 of the present invention. Detailed Embodiments
[0038] The present invention provides a Ni-based composite electroplating solution based on in-situ generation of CeO2 from cerium nitrate, its preparation method and application. In order to make the advantages and technical solutions of the present invention clearer and more definite, the present invention will be further described below in conjunction with specific embodiments.
[0039] The raw materials selected in the present invention can all be obtained through commercial channels.
[0040] The technical concept of the present invention is as follows:
[0041] The present invention realizes Ce deposition in the process of electrodeposition by designing a M-Ce(NO3)3 complex with a specific coordination structure. 3 + The controlled release and oxidation of CeO2 eventually generates uniformly dispersed CeO2 nanoparticles in situ in the nickel-based coating. Specifically, the M-Ce(NO3)2 in the plating solution is in the form of stable Ce 3+ -Exists in the form of organic ligand complexes, inhibiting Ce through coordination bonds 3+ Premature hydrolysis of the complex ensures its long-term stability; during the deposition process, the local pH rises (pH>8) due to the hydrogen evolution reaction on the cathode surface, which promotes the release of Ce 3+ Oxidized to Ce 4+ And hydrolyze to generate CeO2 (reaction formula: 4Ce 3+ +O2+6H2O→4CeO2↓+12H + ). This process is similar to Ni 2+ The reduction deposition rate is dynamically matched, and the steric hindrance effect of the organic ligand inhibits the agglomeration of CeO2 nanoparticles, making them uniformly embedded in the nickel lattice gap. The introduction of M-Ce(NO3)3 significantly enhances cathode polarization, refines nickel grains to ~100nm (conventional coating is ~500nm), and reduces the porosity of the coating to <0.1pores / cm 2 ; In addition, the redox properties of CeO2 The coating is endowed with self-repairing function, and the salt spray resistance time is increased to 376 hours by passivating microcracks, which is more than 2 times higher than the traditional process. This mechanism realizes the preparation of high-performance composite coatings under a single plating solution system through the synergistic effect of electroplating solution component design, dynamic deposition control and coating structure optimization.
[0042] The present invention first prepares M-Ce(NO3)3, and the specific steps are:
[0043] Step 1: 3,4-dihydroxybenzaldehyde and β-alanine are used as raw materials in a molar ratio of 1:1.2. 3,4-dihydroxybenzaldehyde and β-alanine are dissolved in a mixed solvent of ethanol and water in a volume ratio of 7:3. 0.5 mol% pyridine is added as a catalyst. The mixture is stirred and refluxed in a water bath at 60°C under nitrogen protection for 6 hours. During the period, sodium cyanoborohydride (total equivalent 1.5 times) is slowly added three times for reductive amination. After the reaction is completed, the solvent is removed by rotary evaporation. The pH is adjusted to 3-4 with dilute hydrochloric acid to precipitate. After suction filtration, the mixture is recrystallized with a mixed solvent of ethyl acetate / n-hexane (volume ratio 1:5) to obtain white needle-shaped crystals of N-(3,4-dihydroxybenzyl)-β-alanine.
[0044] Step 2: Dissolve N-(3,4-dihydroxybenzyl)-β-alanine and salicylaldehyde in anhydrous ethanol at a molar ratio of 1:1.05. Add 0.1 mol / L acetic acid-sodium acetate buffer solution to adjust the pH to 4-5. Under nitrogen protection, stir magnetically at room temperature (25±2 °C) for 10-15 hours. During the reaction, monitor the formation of Schiff base by thin layer chromatography (TLC, the developing agent is ethyl acetate: petroleum ether = 1:3). After the disappearance of the raw material spots, cool the reaction solution to 4 °C to precipitate yellow crystals. After suction filtration, wash three times with pre-cooled ether and deionized water successively, and dry in vacuum to obtain the target Schiff base compound.
[0045] Step 3: Dissolve the Schiff base compound and cerium nitrate hexahydrate in anhydrous DMF at a molar ratio of 1:1. Stir and react in the dark at a temperature of 50-70 °C for 7-9 h, controlling the Ce 3+ concentration to be 0.1 mol / L. After the reaction, drop the solution into ice ether to induce the precipitation of the complex. After centrifugal collection, wash three times with a mixed solvent of ether / acetone (volume ratio 1:2) to remove the unreacted cerium nitrate. Dry in vacuum at 60 °C for 12 hours to obtain M-Ce(NO3)3.
[0046] In the M-Ce(NO3)3 prepared by the present invention, M represents a modified ligand formed by N-(2-hydroxybenzylidene)-N-(3,4-dihydroxybenzyl)-β-alanine. The product was characterized by Fourier transform infrared spectroscopy (FT-IR) and X-ray diffraction (XRD) ( Figure 1 、 Figure 2 ). The results show that the characteristic functional groups of M (such as imino C=N bond, phenolic hydroxyl O-H stretching vibration and carboxylate symmetric / antisymmetric stretching vibration) appear significantly in the complex, and at the same time, the typical absorption peaks of NO3 - in cerium nitrate (1384 cm -1 ) are retained, indicating that the ligand M is successfully coordinated with Ce 3+ ; the diffraction peak positions of the complex are highly consistent with the standard card of cerium nitrate hexahydrate (Ce(NO3)3·6H2O, JCPDS No. 24-0200), and no impurity peaks appear, proving that the original crystal structure of cerium nitrate is not damaged during the modification process. In summary, M is bonded to the surface of cerium nitrate through coordination to form a structurally stable M-Ce(NO3)3 complex.
[0047] Taking the above M-Ce(NO3)3 as one of the raw materials for preparing the electroplating solution, through its cooperation with other raw materials, the prepared electroplating solution is completely matched with the nickel matrix.
[0048] Example 1:
[0049] The raw materials and ratios of the electroplating solution are as follows:
[0050]
[0051] The preparation method of the electroplating solution is as follows:
[0052] Step 1: Dissolve NiSO4, NiCl2 and H3BO3 in 1 L of deionized water in sequence, and stir until completely transparent;
[0053] Step 2: Add 15 g of M-Ce(NO3)3 to the transparent solution obtained in Step 1, and ultrasonically disperse for 10 - 30 min;
[0054] Step 3: Add 1 g of glucose and 0.05 g of sodium dodecyl sulfate to the ultrasonically dispersed solution obtained in Step 2 in sequence, and magnetically stir for 20 - 40 min;
[0055] Step 4: Adjust the pH of the reaction solution obtained in Step 3 to 3.8 - 4.2 with 2% ammonia water, and let it stand and age for 24 h to obtain the electroplating solution.
[0056] Figure 3 This is the surface structure and cerium element content in Example 1 of the present invention; The Ni-CeO2 composite film was prepared by electroplating with the above electroplating solution, and the specific electroplating process parameters are shown in Table 1.
[0057] Table 1
[0058]
[0059]
[0060] Example 2:
[0061] The raw materials and proportions of the electroplating solution are as follows:
[0062]
[0063] The preparation method of the electroplating solution and the specific electroplating process parameters are the same as those in Example 1. Figure 4 This is the surface structure and cerium element content in Example 2 of the present invention.
[0064] Example 3:
[0065] The raw materials and proportions of the electroplating solution are as follows:
[0066]
[0067] The preparation method of the electroplating solution and the specific electroplating process parameters are the same as those in Example 1. Figure 5 This is the surface structure and cerium element content in Example 3 of the present invention.
[0068] Comparative Example 1:
[0069] The raw materials and proportions of the electroplating solution are as follows:
[0070]
[0071]
[0072] The preparation method of the electroplating solution is the physical mixing method, and the specific steps are as follows:
[0073] Step 1: Dissolve NiSO4, NiCl2 and H3BO3 in 1 L of deionized water in sequence, and stir until completely transparent;
[0074] Step 2: Add 3 g of glucose, 0.15 g of sodium dodecyl sulfate and 3 g of CeO2 nanoparticles to the transparent solution obtained in Step 1 in sequence, and stir magnetically for 20 - 40 min;
[0075] Step 3: Adjust the pH of the reaction solution obtained in Step 2 to 3.8 - 4.2 with 2% ammonia water, and let it stand and age for 24 h to obtain the product.
[0076] Figure 6 For the surface structure and cerium element content in Comparative Example 1. The nickel thin film was prepared by electro-deposition using the electroplating solution prepared in this comparative example, and the electroplating process parameters are shown in Table 2.
[0077] Table 2
[0078]
[0079] Comparative Example 2:
[0080] The raw materials and ratios of the electroplating solution are as follows:
[0081]
[0082] The preparation method of the electroplating solution is:
[0083] Step 1: Dissolve NiSO4, NiCl2 and H3BO3 in 1 L of deionized water in sequence, and stir until completely transparent;
[0084] Step 2: Add 3 g of glucose and 0.15 g of sodium dodecyl sulfate to the transparent solution obtained in Step 1 in sequence, and stir magnetically for 20 - 40 min;
[0085] Step 3: Adjust the pH of the reaction solution obtained in Step 2 to 3.8 - 4.2 with 2% ammonia water, and let it stand and age for 24 h to obtain the product.
[0086] The nickel thin film was prepared by electro-deposition using the electroplating solution prepared in this comparative example, and the electroplating process parameters are shown in Table 3.
[0087] Table 3
[0088]
[0089] Comparative Example 3:
[0090] The raw materials and their proportions of the first-layer electroplating solution are as follows:
[0091]
[0092] The preparation method of the electroplating solution is as follows:
[0093] Step 1: Dissolve NiSO4, NiCl2, and H3BO3 in 1 L of deionized water in sequence, and stir until completely transparent;
[0094] Step 2: Add 3 g of glucose and 0.15 g of sodium dodecyl sulfate to the transparent solution obtained in Step 1 in sequence, and magnetically stir for 20 - 40 min;
[0095] Step 3: Adjust the pH of the reaction solution obtained in Step 2 to 3.8 - 4.2 with 2% ammonia water, and let it stand and age for 24 h to obtain the electroplating solution.
[0096] The raw materials and their proportions of the second-layer electroplating solution are as follows:
[0097]
[0098]
[0099] The preparation method of the electroplating solution is as follows:
[0100] Step 1: Dissolve NiSO4, NiCl2, and H3BO3 in 1 L of deionized water in sequence, and stir until completely transparent;
[0101] Step 2: Add 2 g of sodium benzenesulfinate to the transparent solution obtained in Step 1, and magnetically stir for 20 - 40 min;
[0102] Step 3: Adjust the pH of the reaction solution obtained in Step 2 to 3.8 - 4.2 with 2% ammonia water, and let it stand and age for 24 h to obtain the electroplating solution. The nickel thin film is prepared by electro-deposition method using the electroplating solution prepared in this comparative example, and its electroplating process parameters are shown in Table 4.
[0103] Table 4
[0104]
[0105] The porosity, salt spray resistance, compactness and other properties of the thin films prepared in the above examples and comparative examples are tested, and the results are shown in Table 5:
[0106] Table 5
[0107]
[0108] The parts not described in the present invention can be realized by referring to the prior art.
[0109] It should be noted that those of ordinary skill in the art should recognize that the above embodiments are only used to illustrate the present application, rather than to limit the present application. As long as it is within the scope of the essential spirit of the present application, appropriate changes and variations made to the above embodiments should fall within the scope of protection of the claims of the present application.
Claims
1. A Ni-based composite electroplating solution for in-situ generating CeO2 based on cerium nitrate, characterized in that, The raw materials and their ratios used are as follows: The preparation method of the described M-Ce(NO3)3 is as follows: Step 1: Using 3,4-dihydroxybenzaldehyde and β-alanine as raw materials, with pyridine as a catalyst, stirring and refluxing in a water bath under nitrogen protection for a certain period of time. Then, sodium cyanoborohydride is added to the obtained raw material solution in portions for reductive amination reaction to prepare N-(3,4-dihydroxybenzyl)-β-alanine in the form of white needle crystals. Step 2: Dissolve the described N-(3,4-dihydroxybenzyl)-β-alanine and salicylaldehyde according to a certain ratio, and react under nitrogen protection at a pH of 4 - 5 to obtain a Schiff base compound. Step 3: Dissolve the Schiff base compound and cerium nitrate hexahydrate in anhydrous DMF according to a certain molar ratio, and stir and react in the dark at a temperature of 50-70 °C, controlling the Ce 3+ concentration to be 0.1 mol / L. Add the resulting reaction solution to ice ether to induce the precipitation of the complex, remove the unreacted cerium nitrate, and obtain M-Ce(NO3)3 after vacuum drying.
2. The Ni-based composite electroplating solution for in-situ generating CeO2 based on cerium nitrate according to claim 1, characterized in that: In Step 1, the molar ratio of 3,4-dihydroxybenzaldehyde to β-alanine is 1:1.
2. 3,4-dihydroxybenzaldehyde and β-alanine are dissolved in a mixed solvent, and the described mixed solvent includes ethanol and water. The solvent of the reactant obtained from the reductive amination reaction is removed by rotary evaporation, the pH is adjusted to 3 - 4 to precipitate, and after filtration, it is recrystallized with a mixed solvent of ethyl acetate and n-hexane to obtain N-(3,4-dihydroxybenzyl)-β-alanine.
3. A Ni-based composite electroplating solution for in-situ generating CeO2 based on cerium nitrate according to claim 1, characterized in that: In Step 2, the molar ratio of N-(3,4-dihydroxybenzyl)-β-alanine to salicylaldehyde is 1:1.05, and it is dissolved in absolute ethanol; the reaction is carried out at room temperature for 10 - 15 h under nitrogen insulation to obtain a Schiff base compound.
4. A Ni-based composite electroplating solution for in-situ generating CeO2 based on cerium nitrate according to claim 1, characterized in that: In Step 3, the Schiff base compound and cerium nitrate hexahydrate are mixed according to a molar ratio of 1:1, and the coordination process is monitored in real time by ultraviolet-visible spectroscopy during the reaction; the unreacted cerium nitrate is removed by washing with a mixed solvent of ether and acetone.
5. A Ni-based composite electroplating solution for in-situ generating CeO2 based on cerium nitrate according to claim 2, characterized in that: The volume ratio of ethanol to water is 7:3; the water bath temperature is 50 - 70 °C, and the stirring and refluxing time is 5 - 7 h.
6. A Ni-based composite electroplating solution for in-situ generating CeO2 based on cerium nitrate according to claim 2, characterized in that: Sodium cyanoborohydride is added in three portions, and the pH is adjusted to 3 - 4 with hydrochloric acid to precipitate; the volume ratio of ethyl acetate to n-hexane is 1:
5.
7. A Ni-based composite electroplating solution for in-situ generating CeO2 based on cerium nitrate according to claim 3, characterized in that: In Step 2, the pH is adjusted to 4 - 5 by adding an acetic acid-sodium acetate buffer solution.
8. A Ni-based composite electroplating solution for in-situ generation of CeO2 based on cerium nitrate according to claim 4, characterized in that: In Step 3, the vacuum drying temperature is 10 - 14 h.
9. The preparation method of a Ni-based composite electroplating solution for in-situ generating CeO2 based on cerium nitrate according to any one of claims 1 to 8, characterized in that, It includes the following steps: Step 1: Dissolve NiSO4, NiCl2, and H3BO3 in deionized water in sequence and stir until transparent. Step 2: Add M-Ce(NO3)3 to the transparent solution obtained in Step 1 and ultrasonically disperse for 10 - 30 min. Step 3: Add glucose and sodium dodecyl sulfate to the ultrasonically dispersed solution obtained in Step 2 in sequence and magnetically stir for 20 - 40 min. Step 4: Adjust the pH of the reaction solution obtained in Step 3 to 3.8 - 4.2 and let it stand and age for 24 h to obtain the product.
10. Use of a Ni-based composite electroplating solution for in-situ generation of CeO2 based on cerium nitrate according to any one of claims 1 to 8, characterized in that, The application described is to deposit the electroplating solution on the surface of the nickel substrate by electroplating and form a coating. By controlling the electroplating time within 20 to 30 minutes and the current density at 4 to 6 A / dm 2 , a dense coating with a thickness of 15 to 25 μm is obtained, and the porosity is < 0.1 pores / cm 2 .